The relationship of blood pressure and self care behavior on the quality of life in elderly - Anak Agung Istri Trisia Anggunningrat; Ari Wibawa; Putu Ayu Sita Saraswati (Physical Therapy Journal of Indonesia, 2024)
Background: Several factors, including blood pressure and self-care behavior, influence quality of life in the elderly. Self-care behavior involves taking action to improve and maintain one's health. This study aimed to determine whether there was a relationship between blood pressure and self-care behavior on the quality of life of the elderly in Bali. Methods: This study used an analytical observational design with a cross-sectional approach. The sampling technique used was consecutive sampling. Data was collected by measuring blood pressure with a sphygmomanometer, while self-care behavior and quality of life were measured using a questionnaire instrument WHO Quality of Life-BREF for quality of life and exercise self care agency scale for self care. This study was conducted in Pejeng Village, Tampaksiring District, Gianyar Regency, on April 7, 2023, in the Pejeng 1 State Elementary School classroom. Results: Based on the non-parametric Spearman rho analysis test, the values obtained were p = 0.016 and 0.018 (p<0.05) and the coefficient r = 0.361 and 0.356. Based on the R test, the values obtained are r = 0.612 and r square = 0.375. Based on the T-test, the values of t = 2.180 and 3.331, t table = 2.01954, and p = 0.035 and 0.002. Based on the multicollinearity test, the variance inflation factor value is 1.159. The tolerance value in this study is 0.863. Conclusion: There was a relationship between blood pressure and self-care behavior on the quality of life of the elderly in Bali.